ANALYSIS OF THE INFLUENCE OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) VALUES ON THE VALUE OF MINING COMPANIES IN INDONESIA - Elfitra Alfarizzi, Muhammad
In 2017, OJK issued Financial Services Authority Regulation Number 51 /Pojk.03/2017 clause 10 concerning the Implementation of Sustainable Finance for Financial Services Institutions and Companies where companies are required to prepare Sustainability Reports starting in 2019. Sustainability Reports are a factor in providing information regarding organizational performance through Sustainability Report media. Firm value is used as the main tool in overcoming problems in influencing investors' perspectives. The more the firm value increases, the better the firm's performance. By implementing ESG, it is ensured that ESG becomes a strategic tool for increasing firm value. ESG is a framework used to assess the impact and sustainability of a company based on performance in three aspects, which are social, environmental and governance. The aim of this research is to find the relationship between the ESG value of mining firms and firm value based on the Bloomberg database and firm annual reports with a total of 28 data samples from 7 firms, which are 3 mineral companies and 4 coal companies from 2019 to 2022. This research uses Tobin's Q to measure firm value. Two hypotheses were formulated and tested using Regression Analysis. The analysis is taken from panel data analysis calculations using company data that has been obtained from related companies. The results of the regression analysis in this study concluded that ESG has a significant effect on firm value, but has a negative relationship. In this research, the results of ESG, Size and ROA simultaneously have a significant effect on firm value.